The Effect of Accountability and Transparency of Village Financial Management on Village Government Performancekotarihsergai District - Porkas Sojuangon Lubis; Siti Wardah Pratidina; Winda Wardhani; Widia Wardani; Niken Ilmi Mahmuda Kinder Kinder (Trigin Publisher, 2022)
Qhis study aims to determine whether accountability and transparency in the financial management of village funds, both partially and simultaneously, have a significant effect on the performance of village government in Kotarih Baru Village, Kotarih District, Sergaid Regency, and how big the influence is. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the results of the primary data regression processed using SPSS 20, the multiple linear regression equation is obtained as follows: Y = 6.578 + 0.415 X1 + 0.438 X2. Partially, the accountability variable (X1) has a significant effect on the performance of village government in Kotarih Baru Village, Kotarih District, Regency Sergei. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (2.143> 2.037). Meanwhile, the transparency variable of village fund financial management (X2) has a significant influence on the performance of village government in Kotarih Baru Village, Kotarih District, Sergai Regency. This means that the hypothesis in this study is accepted, as evidenced by the t count > t table (2.173 > 2.037). Simultaneously, the variable accountability (X1) and transparency of financial management of village funds (X2) has a significant influence on the performance of village government in Kotarih Baru Village, Kotarih District, Sergai Regency. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (18,489 > 3.29).